KONSEPTUALISASI SISTEM PENDIDIKAN MENURUT PEMIKIRAN IMAM AL-GHAZALI - Al Ghifari, Barkah; Saprianingsih , Sri Whenti; Harto, Kasinyo; Putra Pratama, Irja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Imam Al-Ghazali's background as a Sufi, a religious expert, and prioritizing noble morals greatly influenced him in all his thoughts, including Islamic education. The journey of Islamic education that has grown and developed until now is greatly influenced by the thoughts of the driving figures in implementing the learning system in his educational institutions. The research method used is descriptive qualitative with literature data collection techniques (library research). Imam Al-Ghazali, a great scholar in Islamic history, is known for his profound thoughts in various fields, including education. In his work, Al-Ghazali emphasized the importance of character formation, moral development, and balance between worldly knowledge and the afterlife. Although Al-Ghazali lived in the 11th century, the concept of the educational system proposed is related to education today. One of the similarities lies in the concept of using reinforcement and punishment in the learning process. The results of this analysis show that there is a match between the concept of the educational system according to Imam Al-Ghazali's thoughts and current education, especially in terms of character formation through positive and negative reinforcement. Through this understanding, we can learn that ideal education is one that integrates spiritual and behavioral aspects, by emphasizing the formation of good character in accordance with Islamic teachings.